(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Bangladesh government has imposed a 65-day marine fishing ban since 2015 to conserve marine fisheries, particularly to boost hilsa (Tenualosa ilisha) production. However, the ecological impacts of the marine fishing bans on water quality and hilsa’s growth are not assessed yet. Thus, this study aims to contribute here using data from coastal waters and fish from pre-contacted fishers in the Nijhum Dwip seascape during and outside the fishing ban in 2021 – 2022. Data were analyzed using R software. The measured mean dissolved oxygen, temperature, pH, electrical conductivity, total dissolved solids, and transparency of the sample water were 7.1 ± 1.13 mg/l, 31.1 ± 0.71°C, 8.45 ± 0.07, 40000 ± 2828 μS/cm, 18000 ± 1414 mg/L and 63.5 ± 2.12 cm at 1 week prior to the ban ends (July) and 8.45 ± 0.21 mg/l, 22.35 ± 0.49°C, 8.45 ± 0.07, 20500 ± 1060.66 μS/cm, 10350 ± 212.13 mg/l and 63.5 ± 7.78 cm before the ban starts (February). The values might be varied due to seasonal differences. The mean length (38 cm) and weight (601 g) of sampled hilsa during the ban periodwere comparatively larger than the mean length (29 cm) and weight (229 g) of hilsa which were sampled during the outside fishing ban period. Therefore, this study concludes that the marine fishing ban has positive impact on the growth and size of hilsa. This study suggests that further research is required to assess the fishing ban’s impact on the growth and production of other coastal and marine fish species across the Bay of Bengal. Dhaka Univ. J. Biol. Sci. 32(1): 33-43, 2023 (January)